1982
DOI: 10.1002/ar.1092030114
|View full text |Cite
|
Sign up to set email alerts
|

A cellular investment of bone marrow

Abstract: We describe a method for clearly separating the cell layers at the bone-marrow interface, which reveals that the myeloid tissue is invested by an epithelial-like layer of specialized squamous cells we call the marrow sac. The scanning electron microscope showed that the sac was fenestrated and that some of its cells pass as perivascular elements with the marrow capillaries that penetrate the bony cortex. The transmission electron microscope (TEM) showed that the cells comprising the marrow sac are less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

1984
1984
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…The bone marrow cells directly exposed to the osteogenic signals released by the osteoclast are the mesenchymal cells that form an envelope surrounding the red bone marrow 181920. They were identified in all species investigated so far,18 and recently received new attention 2122.…”
Section: Overview Of the Putative Effector Cells Of The Reversal Phasmentioning
confidence: 99%
See 2 more Smart Citations
“…The bone marrow cells directly exposed to the osteogenic signals released by the osteoclast are the mesenchymal cells that form an envelope surrounding the red bone marrow 181920. They were identified in all species investigated so far,18 and recently received new attention 2122.…”
Section: Overview Of the Putative Effector Cells Of The Reversal Phasmentioning
confidence: 99%
“…They form an envelope surrounding the whole bone marrow 18192021. Importantly, these cells can differentiate into mature osteoblasts, as shown in culture experiments performed with cells isolated from the bone marrow envelope of human bone marrow plugs 21.…”
Section: Bone-remodeling Compartment Canopiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the multilayered cells is unclear. (14) Since the cell density decreased 3 days after loading, these cells might return to their original position or undergo apoptosis. This might be analogous to the loss of cells on completion of bone remodeling units in humans, amounting to 70% in cortical bone, and 30% in trabecular bone, which remains a well recognized but unexplained observation.…”
Section: Discussionmentioning
confidence: 99%
“…We refer to this as the 'Marrow Sac' (Menton et al, 1982a;McLean and Urist, 1968;Jaffe, 1972;Matthews, 1980). We found that the marrow and endosteal bone cells were each effectively compartmentalized by an intervening condensed surface layer of epithelial-like mesenchymal stromal cells.…”
mentioning
confidence: 99%